1996
DOI: 10.1002/j.1460-2075.1996.tb00862.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DO is a lysosomal resident which requires association with HLA-DM for efficient intracellular transport.

Abstract: The murine MHC class II molecule H2-0 is expressed in B-cells and in thymic epithelium but the human equivalent, HLA-DO (DO), has not been detected, though the corresponding genes, HLA-DNA and HLA-DOB, are well known. Here we show DO to be a lysosomal resident in B-cells. Surprisingly, DO forms stable complexes with HLA-DM (DM), another lysosomal class 11-like molecule which is important for class IT-restricted antigen presentation. Association with DM is necessary for efficient exit of DO from the endoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
176
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(188 citation statements)
references
References 36 publications
11
176
0
Order By: Relevance
“…WT B cells showed a time-dependent colocalization of labeled Ag with LAMP1 (Fig. 6, A and B), a resident lysosomal membrane protein (40). The p110␦ mutant B cells showed similar levels of Ag-LAMP1 colocalization (Fig.…”
Section: Ag-bcr Complexes Are Internalized and Targeted To Late Endosmentioning
confidence: 86%
“…WT B cells showed a time-dependent colocalization of labeled Ag with LAMP1 (Fig. 6, A and B), a resident lysosomal membrane protein (40). The p110␦ mutant B cells showed similar levels of Ag-LAMP1 colocalization (Fig.…”
Section: Ag-bcr Complexes Are Internalized and Targeted To Late Endosmentioning
confidence: 86%
“…However, the association between the two subunits was suggested in studies examining DO localization in human B lymphoma cells. DO was shown to accumulate in lysosomes in a DM-dependent fashion, and accumulation depended upon both DN␣ and DO␤ (13). Association between DN␣ and DO␤ also has been demonstrated directly by copurification of baculovirus-expressed proteins (14) and by coimmunoprecipitation of endogenous proteins in PGF B cell lysates (15).…”
mentioning
confidence: 84%
“…Because many laboratories have demonstrated that DM and DO are tightly associated within B lymphocytes (17)(18)(19)(20), we were surprised by this finding. To further investigate the distribution of DM and DO within the endocytic pathway of the B lymphocyte, we analyzed the distribution of DM and DO within the A20 murine B cell line.…”
Section: Trafficking Of Ag-bcr Complexes Through Dm-and Docontaining mentioning
confidence: 94%